A study of math anxiety and math fluency among FCSHD students - Nur Hafizah, Abdul Rahman; Nur Fatihah, Mat Yusoff (2015)
This study was conducted to determine the mathematics anxiety and fluency in using mathematics language among Faculty of Cognitive Sciences and Human Development (FCSHD). The sample (N=270) involved second and third year students from the bachelor’s degree programmes of Cognitive Science, Human Resource Development, and Counselling. Revised Mathematics Anxiety Rating Scale (RMARS) and Fluency Questionnaire were used to examine mathematics anxiety and their fluency in mathematics language. The findings show that there was no significant difference between anxiety and fluency in mathematics language based on gender and programmes of study. However, there was significant results based on previous academic stream. Moreover, there was a significant and negative relationship between components of mathematics anxiety and fluency in mathematics language.